Using the Balance Sheet Approach in Surveillance : Framework, Data Sources, and Data Availability - Pellechio, Anthony (IMF Working Papers; Working Paper ;, 2006)
Recent improvements in statistical methodologies and data availability are facilitating detailed, high-frequency, timely macroeconomic balance sheet analysis. This paper provides practical instruction on how to design the framework to analyze vulnerabilities in a country as well as an overview of data sources that can be employed for this analysis. The paper also discusses how these new datasets are enhancing surveillance activities related to balance sheet vulnerabilities.